Dendrochronological analysis of coniferous trees in avalanche paths of Central Altai (Chuya River basin) - Nikolay I. Bykov; Natalia V. Rygalova; Anna A. Shigimaga (Acta Biologica Sibirica)
The performed dendrochronological analysis of the radial growth of coniferous trees in the avalanche paths of the Chuya River basin (Central Altai) has enabled to define the patterns of avalanche activity in the studied starting zones and the frequency of high-magnitude snow avalanches. It is shown that a tree-ring complex indicator is driving in detection of avalanche activity in specific avalanche paths. We suggest calling it the dendrochronological index of avalanche activity. In some cases, the applied dendrochronological method has helped to identify the cause (factor) of avalanching in the area under study.